Learning located at the level of reading comprehension in students high school - Chavez-Paredes, Rosse Caroline (2019)
The research work entitled Learning located at the level of reading comprehension in students of a particular educational center. Its objective was to explain the effect of Learning situated at the level of reading comprehension in students of the fourth grade of secondary school of the institution where the present study is carried out. The study paradigm was interpretive, the qualitative approach, type of interpretive research, action research design, interpretive method, with a study scenario of 8 fourth-grade students. The technique used was observation, the instruments used were the blog or field diary, the semi-structured interview that were validated. The results were that the application of situated learning improves the levels of reading comprehension, as well as in turn offers other benefits such as meaningful learning and reading habit.